Research on key synchronization problems of mobile communication: technology, standards and testing - Xinyu MIAO; Changjun HU; Hua CHENG (Dianxin kexue)
The synchronization problem in the existing mobile communication network was studied from three perspectives: technology, standard and testing.It includes the research on the synchronization principle of wireless side, the analysis of the impact of synchronization anomaly on wireless service, and the comparison and difference analysis of synchronization standards between wired side and wireless side, etc.Aiming at the above problems, the corresponding solutions were proposed, including wireless side synchronization performance testing, monitoring methods and synchronization standard revision, etc., to ensure the normal operation of mobile communication synchronization system.